Application model for technological business incubators in universities and educational institutions - Ali, Huda Abdulredha (The journal of contemporary issues in business and government, 2021)
Lethargy and boredom have afflicted the traditional local tools that harness public budgets for the implementation of huge vital projects related to infrastructure. These tools are no longer able to encourage the transfer of the productive capacity of large enterprises to new places. International developments provide wide options for growth in developing countries, but these options depend on the market-oriented and technology-oriented strategies they adopt simultaneously. The experiences of developed countries confirm that stable economic growth rates come in the long run from the union of entrepreneurship and innovation, on the one hand. On the other hand, it means developing new products with traditional entrepreneurship, that is, adapting new products to foreign markets. Entrepreneurs are parties who can accelerate the process of generating, disseminating and applying innovative ideas. The country in which entrepreneurial activities abound seems to be a permanent generator of new and advanced products and services. Research objective: The research aims to Knowing the concept and mechanism of implementing business incubators at the level of organizations in general. Learn about the role of business incubators in universities and the extent to which they can be used in developing the potential of the industrial sector, whether in the production or marketing side.